Beneficial Effects of Viable and Heat-Inactivated Lactobacillus rhamnosus GG Administration on Oxidative Stress and Inflammation in Diet-Induced NAFLD in Rats - Laura Arellano-García; Jenifer Trepiana; J. Alfredo Martínez; María P. Portillo; Iñaki Milton-Laskibar (Antioxidants, 2023)
Oxidative stress and inflammation are well-known triggers of NAFLD onset and progression. The aim of this study is to compare the potential benefits of a viable probiotic (Lactobacillus rhamnosus GG) and its parabiotic (heat-inactivated) on oxidative stress, inflammation, DNA damage and cell death pathways in the liver of rats featuring diet-induced NAFLD. The consumption of the steatotic diet led to increased final body and liver weights, higher hepatic triacylglycerol content, altered serum transaminase levels and enhanced oxidative and inflammatory status. Administration of the probiotic and the parabiotic partially prevented the body weight increase induced by the steatotic diet, whereas the probiotic caused more effective decreasing hepatic triglyceride content. Sharp but nonstatistically significant decreases in serum transaminase levels were also observed for both treatments. The reduction in antioxidant enzyme activities found in the nontreated animals fed the steatotic diet was partially prevented by both treatments (GPx activity). Similarly, the reductions in nonenzymatic antioxidant protection (GSH content) and total antioxidant capacity (ORAC) found in the nontreated rats were restored by the administration of both treatments. These results show that both viable and heat-inactivated Lactobacillus rhamnosus GG administration partially prevent steatotic diet-induced liver oxidative stress and inflammation induced in rats.